(3TQM MOjK CHj EeGeg Ef CZHW ChdjGFis - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG TQM Ydi MOjK CHj EeGeI bGd QShd Gddg Udi Gddg Ydjg hSde Ef CZHW ChdjGFi YfOi deDef Maja GdMGP Ph MX ef GdUdGI CMSf YHGOI QHg hCWGYg ai GdSQ s
(3BNQgG (B:s
(3hbO GTJed gPG GdMOjK Ydi gPg GdCehQ GdegeI aef MaXgG hYed HgG aGR HGdSYGOI GdCHOjI hEfg jgOi ef jTGA Edi UQGW eSJbje s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdMOjK h GdeUWdMs